MODERNISASI BERAGAMA DALAM BUKU PAI SMA DAN SMK - Anhar Caniago (UNISAN JURNAL, 2024)
This examination means to look at endeavors to reinforce the Islamic strict training learning educational program in view of strict balance. This exploration was composed in view of a writing survey and top to bottom comprehension and gathered understanding from different believed essential book sources. This kind of exploration is subjective with a library research approach. Information assortment strategies are completed utilizing documentation. Information sources come from books and diaries. The information investigation strategy utilizes content examination. The examination results demonstrate the way that in light of the past clarification it tends to be reasoned that strict balance is a comprehension of religion that is exceptionally important with regards to variety in all viewpoints, including religion, schooling, customs, identity and country. Reinforcing strict control should be possible through a model based instructive educational plan that moves philosophical qualities to understudies. The upsides of strict control ought to constantly be imparted in strict networks so they can be lenient, fair and adjusted in building inner relations between strict networks and outside relations between individuals of various religions. Thusly, instructive foundations are expected to assume a functioning part in endeavors to assimilate strict balance so understudies can carry out these qualities in public activity. Aside from that, instructive organizations should continually screen and assess the improvement of their understudies and understudies as a work to forestall deradicalization of the universe of schooling. Islamic strict training learning should underscore social instruction, the development of strict control which centers around the fundamental objective of regarding others and oneself. Also, should know about worldwide issues while as yet focusing on moderate and lenient qualities and showing the personality of Rahmatan lil 'alamin.